Prevalence and antimicrobial resistance of methicillin resistant Staphylococcus epidermidis isolated at Mymensingh Medical College Hospital - Haque, N; Bari, MS; Bilkis, L; Hossain, MA; Haque, S; Haque, N; Islam, MA; Mahmud, NU; Kalam, A; Hasan, MS; et al. (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):163-9. The abstract of this article is available on the PubMed website